Penegakan Hukum Terhadap Pelaku Punggutan Liar yang Dilakukan oleh Oknum Aparatur Sipil Negara (ASN) Syahbandar - Cindi M.M Rantung; Jili Tesa Madira; Joice Umboh; Joke Punuhsingon; Kristiane Paendong (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Illegal levies or commonly abbreviated as pungli can be interpreted as levies carried out by individuals or officers who are unlawful and violate the rules. Illegal levies are a form of abuse of authority that has the purpose of facilitating affairs or fulfilling the interests of the levy payer. So it can be concluded that pungli involves two or more parties, be it service users or officers who usually make direct contact to carry out secret or overt transactions, where in general pungli that occurs at the field level is carried out briefly and usually in the form of money. The practice of illegal levies does not only occur in the community but also often occurs in government agencies. Therefore, the following research problems can be formulated: 1. How is law enforcement against illegal levy perpetrators carried out by state civil servants (ASN) syahbandar (Bitung Police Case Study)? 2. How is the application of legal sanctions against illegal levy perpetrators carried out by state civil servants (ASN) syahbandar (Bitung Police Case Study)? The author wrote this thesis using research conducted is normative legal research with an Empirical Juridical approach which uses primary data in the form of interviews with investigators at the Bitung Resort Police and is supported by secondary data, namely primary legal materials, secondary legal materials, and tertiary laws.